ANALYSIS OF THE BOND REPO MARKET IN INDONESIA - Kemal Aditya (Jurnal Riset Ekonomi dan Bisnis, 2021)
This paper aims to examine the role of local currency bond markets repo in Indonesia’s financial market. The role of Bond Repo in Indonesia is mainly for central bank monetary operation and short-term liquidity management by banks. The counterparties in the Indonesia repo market are predominantly the Indonesian central bank and banks. Based on the nature of the transactions and the range of market participants, the bond repo market in Indonesia is still in an early stage of development. This paper also aims to explain the pricing phenomenon of the interbank repo market versus interbank call money in Indonesia Based on market data we have collected from 2016 until June 2021, General Collateral repo rates are priced at a similar level or occasionally higher compared to interbank call money. Repo market research in other countries in Asia has been used as literature reference to help explain the behavior. Factors such as excess liquidity condition, market segmentation, limited market participation, and high dependency on other money market instruments may have influenced this situation.  Penelitian ini mengkaji peran repo obligasi rupiah pada pasar finansial di Indonesia. Peran utama repo obligasi pada pasar finansial di Indonesia adalah sebagai instrumen operasi moneter bank sentral dan instrument pengelolaan likuiditas jangka pendek bank. Pelaku pasar repo di Indonesia didominasi oleh bank sentral dan bank. Berdasarkan pengamatan atas penggunaan transaksi dan sebaran pelaku pasar, repo obligasi di Indonesia termasuk dalam tahap awal pengembangan. Penelitian ini juga mencoba menjelaskan kondisi penetapan harga  pasar repo antar bank versus pasar uang antar bank di Indonesia. Berdasarkan data pasar sejak tahun 2016 hingga Juni 2021, tingkat bunga repo General Collateral berada pada level yang sama atau terkadang lebih tinggi dibandingkan dengan pasar uang antar bank. Penelitian pasar repo di negara Asia lainnya digunakan sebagai referensi literatur untuk membantu menjelaskan kondisi tersebut. Faktor-faktor yaitu kondisi ekses likuiditas, segmentasi pasar, terbatasnya peserta pasar, dan ketergantungan yang tinggi pada instrumen pasar uang lainnya telah mempengaruhi terciptanya situasi dimaksud.